Museum of young arts - Aranas, Lireza Mae D.G. (Manila : National University, 2015)
MOYA will envision as the first interactive art museum experience for children in the Philippines --- nurturing the child$1 (Bcreating a no-fail. The researcher aims to promote arts and culture and tourism, embracing art reflective of the cultural diversity of this modern era, enabling children of diverse ethnicities to build bridges of understanding. The researcher will devote this museum to 21st-century art and artists. MOYA will showcase a Concrete-Bamboo concept that will enrich the sustainable architecture here in the Philippines. Exploring the potential of merging bamboo and concrete, harnessing the strengths of both materials to create a sustainable, durable and affordable material for use in developing countries, like the Philippines. The museum will houses art exhibition galleries, function hall, an outdoor Sculpture Park, music rooms, art rooms and. The museum features to present paintings, sculpture, installations, photography, videos and other media produced since the year 2000.s
Acknowledgement -- Abstract -- Chapter 1. Problem & its setting -- Chapter 2. Research methodology -- Chapter 3. Terms of reference -- Chapter 4. Data gathering & analysis of data -- Chapter 5. Design framework -- Chapter 6. Translations -- Chapter 7. Suggestions, corrections, and final revisions
Includes bibliographical references.